DEVELOPMENT AND CREATION OF A LABORATORY MODEL OF AN INDUSTRIAL OVEN WITH MHD-STIRING FOR ALUMINUM AND ITS ALLOYS - Khripchenko, S.Yu.; Denisov, S.A.; Dolgikh, V.M.; Lekomtsev, S.V.; Pavlinov, A.M.; Oborin, P.A. (Perm Federal Research Centre Journal, 2018)
In this work using physical models of an aluminum furnace bath, the mixing process of a liquid metal with a traveling magnetic field, which is created by a system of parallel linear conductors located under the bottom of the bath, is investigated. The flow velocity profiles and the dependence of the mixing rate on the force and frequency of the current in the inductor were obtained on a gallium model using a Doppler anemometer. In the experiment, a sharp decrease in the vertical temperature gradient in the bath was found when the threshold value of the mixing rate of the liquid metal was reached. With the help of mathematical modeling, the flow pattern, the evolution of the temperature field and the spread of the impurities in the bath of the physical model under MHD stirring are calculated. The results are compared with the results of the physical experiments.